Etiology and clinical features of infection-associated plastic bronchitis in children - Feng Huang; Wenjing Gu; Jianfeng Diwu; Xinxing Zhang; Yanyu He; Youjian Zhang; Zhengrong Chen; Li Huang; Meijuan Wang; Heting Dong; Shanshan Wang; Yuqing Wang; et al. (BMC Infectious Diseases, 2023)
Abstract Objective To investigate the etiological characteristics of plastic bronchitis (PB) caused by pulmonary infections in children and to identify any differences in the clinical features of PB cases caused by different pathogens. Method We collected data on children diagnosed with PB and admitted to the Respiratory Department at Soochow University Children’s Hospital between July 2021 and March 2023 utilizing electronic bronchoscopy. We analyzed clinical characteristics and the species of pathogens causing the illness in these children. Result A total of 45 children were enrolled. The main clinical symptoms observed were cough (100%), fever (80%), shortness of breath (28.9%), and wheezing (20.0%). Pathogens were identified in 38 (84.4%) patients. Mycoplasma pneumoniae (MP) had the highest detection rate at 53.3%, followed by the Boca virus at 26.7%. MP-induced PB typically occurs in older children with an average age of 7.46 ± 2.36 years, with the main symptoms including high fever (85.7%) and local hyporespiration (42.9%). In contrast, Boca virus-induced PB tends to occur in younger children, with the main symptoms of moderate fever (54.5%), and wheezing (54.5%). The MP group exhibited a higher incidence of both internal and external pulmonary complications, including pleural effusion (42.9%), elevated aspartate aminotransferase (52.4%), lactic dehydrogenase (76.2%), and D-D dimer (90.5%). Conversely, the Boca virus group primarily showed pulmonary imaging of atelectasis (81.8%), with no pleural effusion. The average number of bronchoscopic interventions in the MP group was 2.24 ± 0.62, which was significantly higher than that required in the Boca virus group (1.55 ± 0.52). During the second bronchoscopy, 57.1% of children in the MP group still had visible mucus plugs, while none were observed in the Boca virus group. Conclusion MP and Boca virus are the primary pathogens responsible for PB among children. The clinical manifestations of PB typically vary significantly based on the pathogen causing the condition.